1978
DOI: 10.1080/00039896.1978.10667323
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Toxicity of Tobacco Smoke Solutions to Rabbit Alveolar Macrophages

Abstract: The biological activity of various cigarette smokes has been assessed by treating cell cultures of rabbit alveolar macrophages with salt solutions of "whole smoke," smoke "vapor phase," and smoke "particulate phase." The results of these tests revealed degrees of toxicity that varied in accordance with the smoke treatment used. Further, these differences in toxicity were statistically significant at the 95% confidence limit. Observations of changes in cell morphology on exposure to the smoke solutions indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The apoptosis induced in these models was related to an increase in oxidative stress, Bax protein accumulation, mitochondrial dysfunction, and mitochondrial cytochrome c release, but was unrelated to p53, Fas, and caspase activation [142]. CS extract (CSE) led to apoptosis at a lower density (10% to 25%) but to cell death and necrosis at higher density (50% to 100%) [143], confirmed by earlier in vitro studies [144,145]. Machiya and co-workers reported that CS-induced apoptosis in LM was partly dependent on caspase-3, in contrast to the reports of Aoshiba [142].…”
Section: Lm Apotosis Accociated With Cigarette Smoke Exposuresupporting
confidence: 65%
“…The apoptosis induced in these models was related to an increase in oxidative stress, Bax protein accumulation, mitochondrial dysfunction, and mitochondrial cytochrome c release, but was unrelated to p53, Fas, and caspase activation [142]. CS extract (CSE) led to apoptosis at a lower density (10% to 25%) but to cell death and necrosis at higher density (50% to 100%) [143], confirmed by earlier in vitro studies [144,145]. Machiya and co-workers reported that CS-induced apoptosis in LM was partly dependent on caspase-3, in contrast to the reports of Aoshiba [142].…”
Section: Lm Apotosis Accociated With Cigarette Smoke Exposuresupporting
confidence: 65%
“…At room temperature, aqueous smoke solution (tobacco smoke extract) was prepared by putting the smoke from a cigarette through phosphate‐buffered saline as described previously (23). The smoke solution was collected and then adjusted to a pH of 7.4 with sodium bicarbonate water and filtered through a 0.22 µm filter (Millipore Co., Bedford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CS is also known to be toxic to AMs. In in vitro studies, acute CS exposure has been shown to kill AMs (31,35), although the type of cell death, i.e., necrosis or apoptosis, remains uncertain. The mechanism of CS toxicity to AMs may involve oxidative stress, an important mediator of cell death via both necrosis and apoptosis.…”
mentioning
confidence: 99%